Resilient Control of State Synchronization for Nonlinear Multi-Agent Systems Under Exponential Attack Signals⁎This work was supported in part by the National Natural Science Foundation of China under Grants 61873300, 61722312, and in part by the Fundamental Research Funds for the Central Universities under Grant FRF-BD-19-002A. Issue 5 (2020) - Yan, Chunsheng; Zheng, Yongjian; Dai, Xun; Gao, Baiyu; Zhong, Liguang; Xia, Lina; Li, Qing; Song, Ruizhuo
Abstract: The state synchronization problem for nonlinear multi-agent systems (MASs) under attack signals is tackled by designing a resilient controller. Firstly, assuming the attack signal in the sensors and actuators is zero, a conventional controller is designed to ensure the performance and stability of the system. Then, considering the attack signal, we model attacks on sensors and actuators, respectively. A compensation signal is appended on the basis of the conventional controller so that it can absolutely compensate the adverse effects of the attack signal. And then, the resilient controller is given, and the tracking error can be arbitrarily small by adjusting the relative parameters. The theoretical results show that the designed resilient controller can work well even if the attack signal is positive exponential. Finally, a simulation example proves the correctness of the theoretical results.